2017
DOI: 10.1080/19320248.2017.1374902
|View full text |Cite
|
Sign up to set email alerts
|

Self-report vs. direct measures for assessing corn soy blend porridge preparation and feeding behavior in a moderate acute malnutrition treatment program in southern Malawi

Abstract: Rogers (2018) Self-report vs. direct measures for assessing corn soy blend porridge preparation and feeding behavior in a moderate acute malnutrition treatment program in southern Malawi,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Super cereal is prepared from heat treated maize, whole soya beans, vitamins and minerals to provide a highly nutritious meal [34]. A study done in Malawi showed that the provision of super cereal increased calorie density as well as enhancing the absorption of fat-soluble vitamins, thereby addressing the nutritional needs of children with moderate acute malnutrition [35].…”
Section: Discussionmentioning
confidence: 99%
“…Super cereal is prepared from heat treated maize, whole soya beans, vitamins and minerals to provide a highly nutritious meal [34]. A study done in Malawi showed that the provision of super cereal increased calorie density as well as enhancing the absorption of fat-soluble vitamins, thereby addressing the nutritional needs of children with moderate acute malnutrition [35].…”
Section: Discussionmentioning
confidence: 99%
“…Super cereal is prepared from heat treated maize, whole soya beans, vitamins and minerals to provide a highly nutritious meal [32]. A study done in Malawi showed that the provision of super cereal increased calorie density as well as enhancing the absorption of fat-soluble vitamins, thereby addressing the nutritional needs of children with moderate acute malnutrition [33].…”
Section: Discussionmentioning
confidence: 99%
“…They are also expected to know the consequences of malnutrition. However, other than knowledge, the behaviour is also influenced by other factors, such as environment, socioeconomic status, socio-cultural status, and policy (Langlois et al, 2018).…”
Section: Maternal Eating Behavior's Knowledgementioning
confidence: 99%